IDENTIFIKASI DAN ANALISIS KARAKTERISTIK LONGSOR DI KABUPATEN GARUT - Bakri, Subhan; Murtilaksono, Kukuh; Barus, Baba (JURNAL TEKNIK SIPIL, 2019)
Based on the data of earthquake disaster events in Indonesia for the last 12 years then West Java Province was most often experienced landslide disaster. Land movement map of Garut Regency issued by Directorate of Volcanology and Geological Hazard Mitigation (DVMG), indicated Garut included in the category of vulnerability zone of high ground movement, among others: District Banjarwangi, Singajaya and Peundeuy. This study aimed to identify and analyzed the characteristics of landslides in Garut regency, especially in three districts. The first phase of this study conducted a literature study on various factors causing landslides, followed by making a list of fields as a guide in the field. The identification of landslides was done descriptively. Various factors suspected to be the cause of the landslide were identified and analyzed. Based on the results of observation for 14 months at 32 landslide point that occurred in the research area, there were 2 landslide characteristics encountered, namely 1. Soil scrolling (30 cases or 94%) and 2. Decreased / subsidence (2 cases or 6%). The highest landslide was found on paddy fields as much as 25 dots, followed by mixed gardens (talun) as much as four points, in the settlement / infrastructure found two points and one season plantation garden.